2012
DOI: 10.1152/ajpcell.00299.2011
|View full text |Cite
|
Sign up to set email alerts
|

Thin-filament length correlates with fiber type in human skeletal muscle

Abstract: Fowler VM. Thin-filament length correlates with fiber type in human skeletal muscle. Am J Physiol Cell Physiol 302: C555-C565, 2012. First published November 9, 2011; doi:10.1152/ajpcell.00299.2011.-Force production in skeletal muscle is proportional to the amount of overlap between the thin and thick filaments, which, in turn, depends on their lengths. Both thin-and thick-filament lengths are precisely regulated and uniform within a myofibril. While thick-filament lengths are essentially constant across muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(72 citation statements)
references
References 60 publications
3
66
0
Order By: Relevance
“…α-Actinin (ACTN1A) and tropomodulin (TMOD4), which are known I band and A band proteins, respectively, did not change localization in relaxed and contracted muscles (Supplemental Figure 6, A-D, and ref. 32). These data suggested that KLHL40 can localize to either the sarcomere I band or A band and indicated to us a possible role for KLHL40 in the sarcomere.…”
Section: Discovery and Analysis Of Striated Muscle-specific Expressiomentioning
confidence: 54%
“…α-Actinin (ACTN1A) and tropomodulin (TMOD4), which are known I band and A band proteins, respectively, did not change localization in relaxed and contracted muscles (Supplemental Figure 6, A-D, and ref. 32). These data suggested that KLHL40 can localize to either the sarcomere I band or A band and indicated to us a possible role for KLHL40 in the sarcomere.…”
Section: Discovery and Analysis Of Striated Muscle-specific Expressiomentioning
confidence: 54%
“…Indeed, although the relative ratio of Tmods to pointed ends is rather constant (63,65,67), thin filament lengths and the relative ratio of Tmod1 to Tmod4 varies among striated muscle types (10,63,67,85,(100)(101)(102). This suggests functional specialization of sarcomeric Tmods, whose biochemical and structural bases remain to be determined.…”
Section: Summary and Outstanding Questionsmentioning
confidence: 99%
“…Whereas thick filament lengths are essentially constant in all skeletal muscles and species examined (∼1.65 µm), thin filament lengths vary substantially across muscles and vertebrate species (0.95-1.40 µm) (Castillo et al, 2009;Gokhin et al, 2012Gokhin et al, , 2010Granzier et al, 1991;Ringkob et al, 2004). Thin filament lengths are remarkably plastic during normal postnatal skeletal muscle development and aging (Gokhin et al, 2014a) but can become misspecified in some congenital myopathies.…”
Section: Introductionmentioning
confidence: 99%